Effect of Progressive Muscle Relaxation on Sleep Quality and Side Effects of Chemotherapy in Children with Cancer: Randomized Clinical Trial - Sulistyawati, Erna; Allenidekania, Allenidekania; Gayatri, Dewi (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Sleep disturbance affects quality of life in children receiving chemotherapy. AIM: The aim of this study was to identify the effect of progressive muscle relaxation on the sleep quality and side effects of chemotherapy in children with cancer. METHODS: This study used randomized clinical trial with single blind method, where 30 children were allocated randomly to the control group and intervention group. The intervention group received progressive muscle relaxation twice a day, in the morning and evening, 15 minutes each session for 7 days. Control group received routine nursing care. RESULTS: The study concluded there was no significant difference in the two groups on fatigue and pain. However, progressive muscle relaxation had significant relation to decreased sleep quality score. CONCLUSION: Relaxation therapy, particularly progressive muscle relaxation, may be one of the nursing cares to improve sleep quality and reduce the side effects of chemotherapy in children with cancer.